Financial and Operating Performance of Initial Public Offerings in Pakistan - Rafique, Amir; Quddoos, Muhammad Umer; Khadim, Irfan; Tariq, Muhammad (iRASD Journal of Economics, 2020)
This study examines the relationship between prior IPO demands and post-IPO financial and operating performance of ?rms listed in the Pakistan Stock Exchange. A sample of 51 listed firms, covering a period of ten years, is examined. Predominantly, the investors' demand has been analyzed from two perspectives including oversubscription (a high demand from investors as compared to shares offered by firms) and under subscription (a low demand from investors as compared to shares offered by the firm). Multiple regression analysis has been applied, where the findings revealed that investors demand IPO bring no significant change in the financial and operating performance of IPO firms. Moreover, the analysis reveals that firm size, issue size, and leverage bring no notable change in the operating performance of IPO firms. The findings are important for the investors, portfolio managers, and underwriters.